Kielivalinnat ja kielenvaihtaminen ensikielisten ja ei-ensikielisten suomenpuhujien keskusteluissa - Kyselytutkimus - Heikkola, Leena Maria; Toivola, Minnaleena; Kim, Jeongdo; Saloranta, Antti (Suomen Soveltavan Kielitieteen Yhdistys AFinLA ry, 2025)
Immigration into Finland has increased in recent years. Learning Finnish is essential for integrating into Finnish society. We investigated L1 Finnish speakers’ language choices and language switching in everyday conversations with L2 Finnish speakers, and their reasoning for these choices. The data were gathered in an online survey with 358 respondents. The majority of L1 Finnish speakers reported starting conversations with L2 Finnish speakers in Finnish. However, 95% of respondents also reported switching the language of the conversation to English. The reported reasons were efficiency, speed, politeness and the desire to help. Most respondents also assumed that L2 Finnish speakers would react positively to the language switch. The results outline the need for mutual agreement on language choice and switching in everyday discussions. L1 Finnish speakers should understand the importance of offering possibilities to speak Finnish speakers should understand the importance of offering possibilities to speak Finnish to facilitate language learning and to ensure equality in discussions and aid participation in Finnish society.
Puheen tutkimuksen uusia suuntia – Aineistona vapaasti tuotettu puhe